The roles of international entrepreneur orientation and geographical scope level to determine international performance: a case in the Malaysian halal food industry - Ismail, Noor Azlin (Allied Academies, 2017)
Falling trade barriers and innovations in information and communication technology (ICT), particularly the widespread use of the Internet and e-commerce, have provided new opportunities for the internationalization of small and medium-sized enterprises (Knight, 2001). One response to this changing environment is an increasing interest in entrepreneurship. The entrepreneurs are the core decision makers and have the greatest influence on their firms, business strategy and roadmaps formulation, setting the firm’s goals and steering the firm forward (Masurel et al., 2003). They play an important role in economic growth, innovation, competitiveness and poverty alleviation (Kropp et al., 2006).